ROLE OF BAMBOO FOR REVEGETATION OF POST COAL MINING IN SOUTH SUMATERA, INDONESIA - Melisyah, Melisyah; Ibrahim, Eddy; Hanum, Laila; Aprianti, Nabila; Wijayanti, Ratih (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
Coal mining activities have affected the soil and vegetation conditions on the mined land. Revegetation of ex-mining land is a must to balance environmental functions. The choice of plants must be adapted to the conditions of the ex-mining land so that growth continues. The use of local plants for revegetation is fascinating to study. This study aimed to investigate the soil characteristics of ex-coal mining land and bamboo growth as a plant used for revegetation. Bamboo is collected from around the former coal mining area. Bamboo growth is observed through its branching for 12 weeks of measurement. Soil is analyzed based on its physical and chemical properties. The Schmidt-Ferguson method was used to analyze the climate type in the study area. The results of the soil analysis show that the plants can still grow for revegetation. Of the three types of bamboo observed (Schizostachyum brachycladum kurz, Dendrocalamus asper, and Gigantochloa robusta), Schizostachyum brachycladum kurz is the best growing bamboo in ex-coal mining land with a branch length of 42 cm in 12 weeks of measurement. The climate in the ex-coal mining area studied is a wet type (Q = 0.184). Bamboo is a suitable plant for revegetation, especially in coal mining areas in South Sumatra, Indonesia.